The Dharma bums - Kerouac, Jack, 1922-1969 (Penguin classics deluxe edition, 2006)
Two ebullient young men are engaged in a passionate search for dharma, or truth. Their major adventure is the pursuit of the Zen way, which takes them climbing into the high Sierras to seek the lesson of solitude, a lesson that has a hard time surviving their forays into the pagan groves of San Francisco's Bohemia with its marathon wine-drinking bouts, poetry jam sessions, experiments in "yabyum," and similar nonascetic pastimes.